THE IMPLEMENTATION OF ANAGRAM GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT JUNIOR HIGH SCHOOL - Muhammad Khoerul Hadist; Mila Rosdiana (JELLi Journal, 2021)
The objective of the research was to find out whether the implementation of anagram game can improve students’ vocabulary mastery at seventh-grade students of MTS Manbaul Ulum. This research used a quantitative method and cluster sampling technique. The sample of this research was two-class as experimental class and control class, each class consisting of 30 students. The instrument was test. The pre-test and the post-test were given to the experimental class and control class. In this research, the writer used the normality test, and T-test to calculate and analyze data. Based on the data, it was found that the mean pre-test score in the experimental class was 29,53 and in control class was 27,22. Meanwhile, the mean post-test score in the experimental class was 59,46 and in control class was 35,66. For the Normality test, the Chi-Square in experimental class has statistic x² = 4,5 and in control class has statistic x² = 4. While the reference from the Chi-Square table with = 0.05 (5%) and degrees of freedom = 5 is 11,07. It means that the x² table is higher than the x² statistic. The difference between the two tests pre-test and post-test was evaluated using t-test analysis to prove hypothesis, where the significance level was alpha (?) 5% (0.05). The t-statistic 8,416 and t-table 2,021. The t-statistic > t-table means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, the writer concluded that anagram game can improve students’ vocabulary mastery at seventh-grade of MTS Manbaul Ulum